2015
DOI: 10.1007/s13410-015-0367-3
|View full text |Cite
|
Sign up to set email alerts
|

Lack of knowledge about diabetes in Pune—the city of knowledge!

Abstract: India is experiencing an escalating epidemic of diabetes for which the most cost-effective solution is prevention. Awareness is the first step towards prevention. We undertook a questionnaire-based study to evaluate gaps in awareness of different implications of diabetes among various sections of the urban population of Pune. Individuals aged ≥13 years (378 diabetic, 1122 non-diabetic) from different socio-economic backgrounds were interviewed using a structured questionnaire. Awareness regarding causes, sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…4,7 Asian Indians develop DM2 at a younger age and at a lower body mass index compared with western populations. 8 Limaye et al 9 stress the importance of modifications in lifestyle in the prevention of DM2 such as poor diet, physical inactivity, and obesity and that this can only be achieved if individuals' awareness of the preventability and control of the disease is improved. Assessing awareness of preventability and control of DM2 is a critical first step toward designing appropriate health education and intervention programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 Asian Indians develop DM2 at a younger age and at a lower body mass index compared with western populations. 8 Limaye et al 9 stress the importance of modifications in lifestyle in the prevention of DM2 such as poor diet, physical inactivity, and obesity and that this can only be achieved if individuals' awareness of the preventability and control of the disease is improved. Assessing awareness of preventability and control of DM2 is a critical first step toward designing appropriate health education and intervention programs.…”
Section: Introductionmentioning
confidence: 99%
“…10 A more recent study in Chennai showed that knowledge was particularly low in women and the low literate population. 11 There is limited literature on awareness of the preventability and control of DM2 in India, 9 and no studies of college or university students specifically have been reported. University students living in Visakhapatnam, India may represent a population at high risk for diabetes due to factors such as rapid urbanization of the city and other lifestyle factors common among college students that might contribute to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 51 ] Evidence from several studies determining the level of knowledge and awareness on diabetes across India suggests that most of the patients had poor knowledge and awareness about their condition. [ 912 919 920 921 922 923 924 925 ] Low socio-economic status, old age, cultural factors, lack of access to healthcare, family history of diabetes, and importantly low literacy levels were the major predictors of poor glycaemic control among patients with T2DM. A cross-sectional, questionnaire-based survey was conducted in 100 patients attending the diabetic unit of a tertiary care teaching hospital in central India.…”
Section: Rational and Evidencementioning
confidence: 99%
“…Plasma glucose, triglyceride, total cholesterol and HDL cholesterol levels were measured using standard kits (coefficient of variation <4%). A pretested questionnaire was used to record demographic details, medical and family history, lifestyle recall (diet, physical activity and substance use) and awareness of diabetes .…”
Section: Methodsmentioning
confidence: 99%